A Middle to Late Miocene Trans-Andean Portal: Geologic Record in the Tatacoa Desert - Montes, C.; Silva, C. A.; Bayona, G. A.; Villamil, R.; Stiles, E.; Rodriguez-Corcho, A. F.; Beltran-Triviño, A.; Lamus, F.; Muñoz-Granados, M. D.; Pérez-Angel, L. C.; Hoyos, N.; Gomez, S.; et al. (Frontiers in Earth Science, 2021)
Integration of several geologic lines of evidence reveals the prevalence of a lowland trans-Andean portal communicating western Amazonia and the westernmost Andes from at least middle Miocene until Pliocene times. Volcanism and crustal shortening built up relief in the southernmost Central and Eastern Cordilleras of Colombia, closing this lowland gap. Independent lines of evidence consist first of field mapping in the Tatacoa Desert with a coverage area of ~381 km2, 1165 km of geological contact traces, 164 structural data points, and 3D aerial digital mapping models. This map documents the beginning of southward propagation of the southernmost tip of the Eastern Cordillera's west-verging, fold-and-thrust belt between ~12.2 and 13.7 Ma. Second, a compilation of new and published detrital zircon geochronology in middle Miocene strata of the Tatacoa Desert shows three distinctive age populations: middle Miocene, middle Eocene, and Jurassic; the first two sourced west of the Central Cordillera, the latter in the Magdalena Valley. Similar populations with the three distinctive peaks have now been recovered in western Amazonian middle Miocene strata. These observations, along with published molecular and fossil fish data, suggest that by Serravallian times (~13 Ma), the Northern Andes were separated from the Central Andes at ~ 3°N by a fluvial system that flowed into the Amazon Basin through the Tatacoa Desert. This paleogeographic configuration would be similar to a Western Andean, or Marañon Portal. Late Miocene flattening of the subducting Nazca slab caused the eastward migration of the Miocene volcanic arc, so that starting at ~ 4 Ma, large composite volcanoes were built up along the axis of today's Central Cordillera, closing this lowland Andean portal, and altering the drainage patterns to resemble a modern configuration.